Basic syntactic concepts of Latin to access classical texts - Gispert-Sauch Colls, Ana María (2014)
The present study tries to clearly formulate the syntactic concepts necessary to understand and interpret classical Latin texts, as well as philosophical, historical or literary texts, compulsory in university humanistic studies.The study of the Latin language entails the conjunction of two essential aspects of language: its morphology (regarding Latin, with its nominal, adjectival and pronominal declensions, as well as the paradigms of verb conjugations) and syntax, that is, the characteristic rules of its structure, its expressions, and its possibilities.In this study we do not take into account the morphological rules as they are already known. We formulate instead the syntactic combinations of the four essential grammatical categories: the noun, the adjective, the verb and the adverb. We go in depth in the peculiarity of each function, as well as other syntactic forms that can also perform such functions.